Labour law and poverty alleviation datasets - Deakin, Simon F. (UK Data Service, 2016)
This data collection consists of (1) a leximetric dataset coding for labour laws in 117 countries for the period 1970-2013, consisting of a PDF document setting out the coding methodology and sources, and an Excel spreadsheet with the data; and (2) qualitative datasets based on interviews in Cambodia, China, South Africa and India; the aim of the project was to understand the role of labour law in alleviating poverty in developing countries. The quantitative dimension of the work took the form of econometric analysis of data on legal and institutional variables. The qualitative dimension of the work consisted of interviews in the case study countries (China, Cambodia, India and South Africa). Interviewees included those with legal knowledge and experience (judges, lawyers, politicians, regulators, civil servants, labour inspectors), private-sector firm-level actors (HR and other managers), and actors in civil society (trade unions, NGOs).